PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, STRUKTUR ASET, LIKUIDITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL (Studi pada Perusahaan Property dan Real Estate pada Tahun 2017-2019) - Theresia Fanny Lia Hanbo; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2022)
This research aims to examine the effect of Profitability, Firm Size, Asset Structure, Liquidity, and Business Risk on the Capital Structure in Property and Real Estate Company Listed in 2017-2019. This research used Property and Real Estate companies listed on Indonesia Stock Exchange from 2017-to 2019 as the research data. This Research is a type quantitative. Purposive Sampling Method for determining the sample, and obtained 30 companies for three years, so it used 90 observations as a sample. This research used multiple regression analysis with secondary data from the annual report of Property and Real Estate Company. The results indicate that the asset structure significantly affects the capital structure. While Profitability, company Size, Liquidity and Business Risk have no significant effect the capital structure. This research model provides a coefficient of determination of 15%. The rest is explained by other variables that are not in the model.